(untitled) - Light, Mark (New York, 2001)
The Strategic Board provides the answer. Drawing on more than twenty years of nonprofit experience, Mark Light outlines a practical model that overcomes the built-in deficiencies of nonprofit boards and guides them to strategic effectiveness. The Strategic Board(TM) model of governance is a step-by-step, easy-to-implement, multilevel course of action that enables a board to craft a comprehensive Governance Plan(TM) that: Develops a Leadership Plan that determines "Where to go tomorrow?"; Creates a Delegation Plan that specifies "Who does what?"; Follows through with a Management Plan that decides "What gets done today?"; Puts in place a Vigilance Plan to answer the question "Did it happen?".
Keywords: Kế hoạch chiến lược,Strategic planning,Nonprofit organizations,Boards of directors,Tổ chức phi lợi nhuận; Management